Analysis of Effect of Profitability, Capital, Risk Financing, the Sharia Supervisory Board and Capabilities Zakat in Islamic Perspective with Circular Approach Causastion on Islamic Banks in Indonesia - Yusnita, Raja Ria; Basri, Yuzwar Z; Mariyanti, Tatik; Zulhelmy; Arafah, Willy (The Economics and Finance Letters, 2019)
This study aimed to analyze the effect of profitability, capital, financing risks, the ability of Sharia supervisory boards and zakat from an Islamic perspective in the circular causation approach, on Sharia banks in Indonesia. This study used a methodology to integrate the TSR of interaction, integration, and evolustion (IIE) to produce factors that affect the ability of zakat and the factors that affect the profitability of Indonesian Islamic banks. The study used the purposive sampling method with a sample of five Islamic banks from 2014 until 2017. This study uses Two Stage Least Square (2SLS) analysis to solve the problem with the Eviews program. The results demonstrated that the ability of zakat can be influenced by profitability, risk financing and capital while the Sharia supervisory board does not have a significant effect on the zakat capability. Profitability may be affected by the ability of zakat, risk financing and capital but not the Sharia supervisory board. The implications show that there is a simultaneous relationship between the ability of zakat and profitability. We recommend that Islamic banks that adhere to Islamic principles should not be afraid to issue zakat as the tithe does not diminish but increases wealth.